Centennial-scale lake-level lowstand at Lake Uddelermeer (The Netherlands) indicates changes in moisture source region prior to the 2.8-kyr event. (July 2016) - Engels, S; Bakker, MAJ; Bohncke, SJP; Cerli, C; Hoek, WZ; Jansen, B; Peters, T; Renssen, H; Sachse, D; van Aken, JM; van den Bos, V; van Geel, B; et al.
The Uddelermeer is a unique lake for The Netherlands, containing a sediment record that continuously registered environmental and climatic change from the late Pleistocene on to the present. A 15.6-m-long sediment record was retrieved from the deepest part of the sedimentary basin and an age–depth model was developed using radiocarbon dating, 210 Pb dating, and Bayesian modeling. Lake-level change was reconstructed using a novel combination of high-resolution palaeoecological proxies (e.g. pollen, non-pollen palynomorphs, chironomids), quantitative determinations of lake-level change (ground-penetrating radar), and estimates of changes in precipitation (lipid biomarker stable isotopes). We conclude that lake levels were at least as high as present-day water levels from the late glacial to 3150 cal. yr BP, with the exception of at least one lake-level lowstand during the Preboreal period. Lake levels were ca. 2.5 m lower than at present between 3150 and 2800 cal. yr BP, which might have been the result of a change in moisture source region prior to the so-called 2.8-kyr event. Increasing precipitation amounts around 2800 cal. yr BP resulted in a lake-level rise of about 3.5–4 m to levels that were 1–1.5 m higher than at present, in line with increased precipitation levels as inferred for the 2.8-kyr event from nearby raised bog areas as well as with reconstructions of higher lake levels in the French Alps, all of which have been previously attributed to a phase of decreased solar activity. Lake levels decreased to their present level only during recent times, although the exact timing of the drop in lake levels is unclear.